The WIL (Work Integrated Learning) report : a national scoping study. - Patrick, Carol-joy; Peach, Deborah; Pocknee, Catherine; Webb, Fleur; Fletcher, Marty; Pretto, Gabriella (Queensland University of Technology, 2009)
'This report provides an account of the first large-scale scoping study of work-integrated learning (WIL) in contemporary Australian higher education. The explicit aim of the project was to identify issues and map a broad and growing picture of WIL across Australia and to identify ways of improving the student learning experience in relation to WIL.' [Executive summary]